Stability and phase behavior of fish oil emulsion containing konjac glucomannan in goat milk systems - Siriwan Suknicom; Chaleeda Borompichaichartkul (Journal of Current Science and Technology, 2021)
We investigated the effects of konjac glucomannan (KGM) solution (0.02%-0.5%, w/w) at different pH (7-10) on the stability of KGM-milk emulsion containing of 5% fish oil. Particle size in the emulsion was increased with the increase in pH values of KGM solution above 7 at all concentrations of KGM. Zeta potential of the emulsion was increased when the pH of KGM solution was increased at all concentration of KGM. The precipitation percentage (0.02%-0.5%) of KGM at any pH was 0%, which stabilized the mixture up to 2 days. However, when the concentration of KGM in the emulsion exceeded 0.5% w/w, precipitation occurred rapidly. The increase in pH values from 7-10 at the same concentration of KGM could increase stability of the emulsion. Confocal laser scanning microscopy images confirmed the assumption that microstructures of KGM-stabilized emulsions were controlled by pH. The images revealed that lowering the pH resulted in expanded appearance of the aggregates. Moreover, the appearance of aggregates changed from isolated cluster to cluster networks, as shown in the emulsion at pH 7 compared to the emulsions at pH 10. Fish oil emulsion containing KGM in milk at different pH and concentration of KGM solution exhibited differences in stability. The mixture stability was enhanced when KGM concentration in solution was decreased and when the pH was increased. The highest stability of the mixture was obtained with 0.02% and 0.04% KGM at pH 9 and 10. The stability of the emulsion with different conditions was due to the merging of steric and electrostatic stabilization.